Triage human papillomavirus testing for cytology-based cervical screening in women of different ages in primary hospitals: A retrospective clinical study. Issue 38 (18th September 2020) - Zhang, Yuan-yuan; Xu, Xiao-qin; Zhang, Dan; Wu, Jie; Zhang, Hong-xiu
Abstract : Abstract: Cervical cancer is a serious global health problem. The objective of this study was to provide a suitable cytology-based cervical screening method in women of different ages in primary hospitals. This study was a retrospective cohort study that included 9765 women who underwent primary cytology-based cervical screening and were grouped by age (35–44, 45–54, and 55–64 years old). Patients with abnormal cytology on the primary cervical thin-prep cytologic test (TCT) were advised to undergo triage human papillomavirus (HPV) test. Furthermore, patients with positive outcomes of the 2 indices underwent cervical tissue biopsy. The positive rate of TCT and HPV was compared among the 3 defined age groups. The sensitivity, specificity, and positive predictive value of TCT and HPV were assessed. In total, 2.5% (241/9765) of women had atypical squamous cells of undetermined significance or worse by TCT. High-risk (HR)-HPV infection was found in 70 triage participants. Neoplastic changes were confirmed in 95 patients (95/437, 21.7%) by biopsies. Among the different age groups, the positive rate of abnormal cytology was significantly different ( P  = .003), and the positive rate of HR-HPV was similar ( P  = .299). The sensitivity of initial TCT testing to detect intraepithelial neoplasia was higher than that of triage HPV testing, whereas the specificity, the positive predictive value of triage HPV testing was higher than that of TCT. The Youden index of HPV testing was higher than that of TCT detection in the 3 age groups, namely 0.582 versus 0.432, 0.553 versus 0.228, and 0.416 versus 0.332, respectively. The results of this study indicate that TCT testing is suitable as a cervical cancer screening method for women ≥35 years old in primary hospitals. Triage testing for women with HR-HPV has a high negative predictive value, reduces the rate of misdiagnosis, seems to be an excellent triage method for repeat atypical squamous cells of undetermined significance, and reduces the number of referral colposcopies preventing unnecessary overtreatment. The results of this study provide a crucial foundation for a unified guideline cervical cancer screening for primary health care institutions.